NON-STERILE M HANDSCOONS INVENTORY CONTROL USING MONTE CARLO SIMULATION: A CASE STUDY - St. Mega Dzulfahra Manguluang; Feri Afrinaldi (Universitas Putera Batam, 2026)
Non-sterile M Handscoons are medical gloves to protect healthcare professionals from transmitting disease through direct patient contact. The handscoons come in boxes at 100 gloves per box. Among all consumable items stocked by Hospital X, located in Padang, the handscoons consumed the highest inventory costs. This paper aims to determine a better inventory policy for the Non-sterile M Handscoons. Better order quantity and reorder point were determined. Since the demand for the handscoon was probabilistic, the Monte Carlo simulation was used to determine the order quantity and reorder point to maximize service level and reasonable total inventory costs. The algorithm used to execute the simulation was presented and implemented as a spreadsheet-based Monter Carlo simulation. Four scenarios were compared, combining different order quantities and reorder points, including the hospital's current inventory control policy. A procedure with the mean of service level and total cost as the criteria for selecting the best scenario was presented. The Anderson-Darling Goodness-of-Fit test and Least Squares parameter estimation method showed that the monthly demand follows Weibull distribution with an estimated shape parameter = 5.32 and scale parameter = 262.06. The monthly demand mean was 242 boxes. Accordingly, using the Central Limit Theorem, the annual demand was approximately normally distributed, with a mean of 2,899 boxes and a standard deviation of about 178 boxes. The simulation results indicated that an inventory policy with an order quantity of 216 boxes and an order interval of 27 days is the most effective. This policy achieved a mean service level of 99.9 percent with an annual inventory cost of Rp179.35 million. In addition, the selected policy was estimated to guarantee a minimum service level of 94.7 percent and achieved a 100 percent service level with approximately 92 percent certainty. Compared with the status quo, adopting this policy increased the service level by approximately 19 percent, accompanied by a proportional increase in annual inventory costs.